Hbr's 10 must reads on managing risk - Review, Harvard Business (Gildan Audio, 2020)
Is your business playing it safe-or taking the right risks'Risk is a regular part of business, but knowing which risks to take and when to step back is often unclear. Whether you're assessing a new opportunity for innovation or thinking about your long-term strategy in an unsteady economy, you need to know the best way to proceed while ensuring that your company is financially secure and thriving.We've combed through hundreds of Harvard Business Review articles and selected the ten most important ones to help you determine which risks are worth taking and mitigate those your company-and your industry at large-are already facing.This book will inspire you to: understand the three categories of risk and tailor your risk-management processes accordingly; gain experience through small strategic bets before launching larger initiatives; embrace uncertainty as a key element of breakthrough innovation; find opportunities in emerging markets-and avoid those you can't practically serve; get ahead of and minimize political risk; and avoid common mistakes when confronting risk.